The humorous discourse and the deconstruction of stereotypes about women in television production (Research, Society and Development, 2021)
This article presents an analysis of jokes, whose discursive object is the woman, with the purpose of discursively analyzing the meaning effects of this deconstruction in the jokes' text. To achieve this purpose, the work is based on the perspective of French Discourse Analysis, from considerations supported by the notions of discourse, discursive formation, production of meaning, stereotypes and the identity of women. The research is based on a descriptive bibliographic study, through which an analysis of five jokes broadcast by the program will be carried out. It was found that jokes are produced based on sexist and stereotyped discourses related to the identity and social role assigned to women, in order to produce meanings that deconstruct these representations. It is possible to affirm that the humorous discourse conveyed by the television program “Zorra” works in the sense of an attempt to deconstruct the stereotyped identity of women, in a different direction than the programs of this television genre, reaffirm these stereotypes.